Peningkatan Hasil Belajar IPAS melalui Media Kahoot pada Siswa Kelas V Sekolah Dasar: Improving IPAS Learning Outcomes through the Use of Kahoot among Fifth Grade Elementary School Students - Arum Mudrika; Soni Yudha Ariyanto; Yasirul Amri (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research was motivated by the low learning outcomes of Natural and Social Sciences (IPAS) for fifth-grade students at SDN 79/VIII Suka Maju Village, Tebo Regency, particularly on the topic of the arrival of foreign nations to Indonesia. The learning process that previously used the Teams Games Tournament (TGT) method had not achieved the expected classical mastery. This study aims to improve IPAS learning outcomes through Kahoot! learning media. The research method was Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, conducted in two cycles. The research subjects were 26 students. Data collection techniques used include learning achievement tests and observation sheets. The results showed a significant improvement. In the pre-cycle, the average student score was only 65.3, with 42.3% mastery. After implementing Kahoot! in Cycle I, the average increased to 74.6 (65.4% mastery), and in Cycle II, it increased dramatically to 85.7 (92.3% mastery). This success was supported by three technical factors: providing tutorials, extending the response time to 30 seconds, and stabilizing the internet connection. This study concludes that Kahoot! Effective learning media improve IPAS learning outcomes for fifth-grade students at SDN 79/VIII Suka Maju Village, Tebo Regency. This study also contributes a modification of the Digital Game-Based Learning theory for rural contexts by adding three key success factors (technical scaffolding, time extension, and offline preparation).